Assessment of the efficacy of drug transdermal delivery by electro-phonophoresis in treating tuberculous lymphadenitis. (12th June 2016) - Chen, Suting; Qin, Ming; Han, Yi; Zhao, Liping; Fu, Yuhong; Shang, Yuanyuan; Liu, Zhidong; Huang, Hairong
Abstract: Electro-phonophoresis (EP) has been used in various clinical fields. The objective of present study is to evaluate the skin permeability of isoniazid (INH) and rifampicin (RIF) in patients with tuberculous lymphadenitis with the aid of EP to validate the clinical applications of this transdermal delivery system for the treatment of superficial extrapulmonary tuberculosis. INH and RIF solutions were delivered transdermally, with or without EP, in the surrounding tissue of the lesion for 0.5 h. Local pyogenic fluids or necrotic tissue samples from the infection sites in patients were collected at 1 h after dosing. Drug concentrations in samples were evaluated by high performance liquid chromatography. The median INH and RIF intra-lesional concentrations were 0.365 (interquartile range [IQR] 0.185–1.775) μg/mL and 1.231 (IQR 0.304–1.836) μg/mL in oral group; 2.964 (IQR 0.193–7.325) μg/mL and 2.646 (IQR 1.211–3.753) μg/mL in INH- and RIF-transdermal plus EP group. Drug concentrations in the local sites of patients receiving INH or RIF through EP transdermal delivery were statistically higher than those observed in patients only taking INH and RIF orally. However, this enhancement was not observed in the transdermal delivery of INH or RIF without EP in contrast to the oral administrations of drugs. EP can effectively enhance the skin permeability of INH and RIF in patients with tuberculous lymphadenitis. The increase in drug concentrations in the lesions could help eradication of the germs; shorten the treatment course and increase the cure rate of patients with tuberculous lymphadenitis.